2015
DOI: 10.1167/iovs.14-15734
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Microstructural Factors Influencing Optic Nerve Head Biomechanics

Abstract: The presence of a heterogeneous collagen fiber organization in the peripapillary sclera appears effective in limiting LC strain and is able to reduce strain levels at the scleral canal boundary: a transition zone prone to LC disinsertion, focal lamina cribrosa defects, and optic disc hemorrhages in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 61 publications
5
98
0
1
Order By: Relevance
“…Lamina cribosas with radially oriented capillaries at the peripheral region had higher average oxygen concentration than those with isotropic or circumferential configurations. Note that human LCs naturally exhibit a radial arrangement of the microcapillaries at the periphery 31 and any deviations from such an arrangement (possible through focal defects 55 ) may contribute to the development of OAG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamina cribosas with radially oriented capillaries at the peripheral region had higher average oxygen concentration than those with isotropic or circumferential configurations. Note that human LCs naturally exhibit a radial arrangement of the microcapillaries at the periphery 31 and any deviations from such an arrangement (possible through focal defects 55 ) may contribute to the development of OAG.…”
Section: Discussionmentioning
confidence: 99%
“…7 To mimic such heterogeneity, all our networks were subdivided into nine regions ( LC Anisotropy. In its periphery, the LC was either considered: (1) anisotropic with a radial arrangement of the LC beams (and thus capillaries) as observed in humans and primates, 31 (2) isotropic (also observed in humans), 31 or (3) anisotropic with a circumferential arrangement (hypothetical scenario). For our LC network generator algorithm, the anisotropy input parameter (r) was defined as the ellipse major-to-minor axis ratio minus 1.…”
Section: Generation Of Artificial Lc Microcapillary Networkmentioning
confidence: 99%
“…1) to account for the circumferential alignment of collagen fibers within the scleral flange and around the scleral canal. 22 Collagen fibers in other scleral regions were organized randomly. The collagen fibers in the LC were more isotropic than in the sclera, but organized along the radial direction (from the central vessel trunk to the scleral canal).…”
Section: Materials Stiffness Of the Reconstructed Eye Tissuesmentioning
confidence: 99%
“…Within this paradigm, IOP-related stresses and strains are thought to affect axoplasmic transport (at the level of the LC), LC hemodynamics, oxygen and nutrient distributions, and cellular activity within the ONH. 3 The compliance of the ONH to acute IOP elevation has been studied using experimental [4][5][6][7][8][9][10][11][12][13][14] and computational models, [15][16][17][18][19] and the findings have varied. Studies using either ex vivo or histologic specimens showed that the LC bowed posteriorly in response to acute IOP elevation.…”
mentioning
confidence: 99%